Community Guidance in the Era of COVID-19 on Children in Conflict with the Law - Shinta Rukmi B; Anggo Doyoharjo (East Asian Journal of Multidisciplinary Research, 2022)
The purpose of this study was to examine and analyze the obstacles that occur in the implementation of the assistance of the Surakarta Penitentiary Community Counselor for Children in Conflict with the Law. The approach method in this writing is sociological juridical. Data collection techniques using interview studies, and observation. To analyze the data, the researcher used a qualitative descriptive analysis method. Based on the results of the study, it was concluded that the Surakarta Penitentiary's Social Advisor for Children in Conflict with the Law was carrying out assistance, guidance, supervision, and Community Research on children in conflict with the law. Assistance at every level of examination is carried out during the implementation of diversion and execution of court decisions or decisions.